Puccinia -Triticum interaction: an update - BHARDWAJ, S.C. (Indian Phytopathology, 2013)
Wheat and rusts have co-existed for decades. A number of genes are known for resistance to wheat rusts. There is a definite interaction between rust and resistance genes. Puccinia-Triticum interaction is very widely researched and a model system guided by gene-for-gene theory. Many of these gene interactions are dependent on light, temperature and growth stage of wheat plants. Complementary, additive and inhibitory gene interactions have been recorded. Evolution and detection of new pathotypes open new horizons and provide material to study evolution in relation to host resistance. An update to our latest understanding on host-pathogens interaction is presented in this review.